Design and simulation for co-ordinated analysis of wind/solar with storage microgrid. (December 2020) - Iqbal, Atif; Ying, Deng; De, Tian; Hayat, Muhammad Aftab; Saleem, Adeel; Jamal, Raheela
Abstract: Energy demand is rapidly increasing with the industrialization and economic growth. Industrialization leads to enhancing global warming along with acid rain, environmental pollution. Therefore, the need for power systems, which composed of alternate energy sources. Mainly, the researchers are contributing to the field of wind and solar power. Wind energy is getting prime importance because of its abundant nature and totally emission free. In addition to it, many researchers are focusing on solar power to enhance its output efficiency, which is very beneficial to fulfill the energy demand. Multi energy systems (MES), which include wind, solar, battery system, and utility grid are used. This paper emphasizes the integration of various energy sources. The research proposes the design of various energy systems such as wind, solar and battery storage along with the utility grid. The sources are coupled and connected to the alternating current (AC) load. The proposed system is designed and simulated by using MATLAB/Simulink. The output power results of the various interconnected sources are satisfactory with the high power quality.